The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/nyas.13447
|View full text |Cite
|
Sign up to set email alerts
|

Dreamless: the silent epidemic of REM sleep loss

Abstract: We are at least as dream deprived as we are sleep deprived. Many of the health concerns attributed to sleep loss result from a silent epidemic of REM sleep deprivation. REM/dream loss is an unrecognized public health hazard that silently wreaks havoc with our lives, contributing to illness, depression, and an erosion of consciousness. This paper compiles data about the causes and extent of REM/dream loss associated with commonly used medications, endemic substance use disorders, rampant sleep disorders, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
(73 reference statements)
0
20
0
1
Order By: Relevance
“…This is apparently linked to the hormonal milieu of the luteal phase, which is characterised by the increased secretion of progesterone (the latter may be implicated in the consolidation of memories [18] and may also alter dreaming during pregnancy [19,20]) but also of altered dynamics in other hormones (see below). Dream recall is reported to be highest for REM dreams [21], thus our finding might be of further importance, given the possible changes in REM sleep frequency, noted as a result of current lifestyle conditions [22]. Cortisol may also have an impact on how emotions are experienced in the process of dream formation [23]; that is, during sleep, cortisol levels peak in the REM phases [23].…”
Section: Discussionmentioning
confidence: 88%
“…This is apparently linked to the hormonal milieu of the luteal phase, which is characterised by the increased secretion of progesterone (the latter may be implicated in the consolidation of memories [18] and may also alter dreaming during pregnancy [19,20]) but also of altered dynamics in other hormones (see below). Dream recall is reported to be highest for REM dreams [21], thus our finding might be of further importance, given the possible changes in REM sleep frequency, noted as a result of current lifestyle conditions [22]. Cortisol may also have an impact on how emotions are experienced in the process of dream formation [23]; that is, during sleep, cortisol levels peak in the REM phases [23].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies reported that alcohol consumption could be an important confounding factor especially for the positive association between long sleep and chronic disease [14,15]. This is because alcohol consumption as well as certain medications increase duration of light sleep at the expense of deep reparative sleep [37]. Qatar is a conservative Muslim country, where alcohol consumption is socially unsanctioned (taboo) practice, which could explain the weak (positive) and statistically non-significant association between long sleep and chronic disease status observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep typically fragments for mammals at the completion of a sleep cycle, which is the stereotypical progression from a vigilant state to REM or NREM sleep, or the dreaming and homeostatic (i.e., deep sleep) states, respectively. However, it should be noted that REM sleep carries a potentially significant homeostatic value (Ephron & Carrington, 1966;Naiman, 2017;Pandey & Kar, 2018;Siegel, 2011). Nonetheless, when sleep cycles-and sleep architecture, in general-are disrupted, as evident by fragmented sleep, homeostasis is compromised (Reid & Zee, 2011).…”
Section: Sleep and Homeostasismentioning
confidence: 99%